Cardiac Impairment in Asphyxiated Newborns Having Hypoxic Ischemic Encephalopathy - Baki, Md Abdul; Akter, Shaheen; Shirin, Mahfuza; Tayab, Md Abu; Hossain, Md Delwar; Hossain, M Monir (Bangladesh Journal of Child Health, 2010)
No abstract available. Bangladesh J Child Health 2006; VOL 30 (1/2/3): 7-11